Obesity and Associated Factors Among Students of Different Medical Colleges in Cumilla During COVID-19 Pandemic - Jannat, S M Khusbul; Karim, Md Razaul; Jannat, Rose Difa; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2025)
Background: The COVID-19 pandemic has led to special situations and changes to daily life due to the worldwide measures that were brought into effect such as lockdowns. Obesity is a major public health concern among medical students which are undesirable health condition and its frequency is high in this Covid -19 pandemic situation. The aim of the study was to assess the state of obesity and associated factors among students of three medical colleges located in Cumilla district during COVID-19 pandemic situation. Methods: This study was a cross-sectional study; Purposive sampling technique was used to select 325 students from three different medical colleges of Cumilla. Data were collected from participants through face-to-face interview using a semi-structured questionnaire after taking informed written consent. Data were analyzed by SPSS software. Results: Among the respondents 52.3% were low, 24.3% were moderate, 24.3%, 12% were high and 11.4% were no physical activity. About 1.8% took one time 12.9% took two times 55.7% took three times 29.5% took their meal more than three times per day. Majority of respondents 54.2% drunk 4 to 6 glasses water daily. Among the 325 participants 12.6% were obese, 21.2% were pre- obesity. Normal BMI was 44.9% and 21.2% was underweight. Obesity was associated with sex; as female medical students were observed to have significantly higher BMI compare to those with male respondents (P<0.000). Family type of the students from joint family were observed more obese than nuclear family, (P<0.05), Dietary pattern. as the BMI of the respondents increased with the increase of frequency of monthly fast food consumption of the respondents (P<0.04). Female medical students were significantly higher biscuits consumption (P<0.03) but male respondent inversely significantly higher in cold drink consumption (P<0.00). Conclusion: The study findings may contribute to developing awareness about weight gain and its long term health consequence and devising interventions to prevent COVID-19 related weight gain among medical students. JOPSOM 2024; 43(2): 53-60